Pendeteksi Posisi Menggunakan Sensor Accelerometer MMA7260Q Berbasis Mikrokontroler ATMEGA 32 - Riyadi, Muhammad; Wahyudi, Wahyudi; Setiawan, Iwan (Transmisi, 2010)
Currently, determining the exact position and orientation in a technical system has an important role, especially in terms of control on a navigation system. One of the instruments used in navigation systems is the Inertial Measurement Unit (IMU). The IMU consists of a combination of the acceleration sensor (accelerometer) and the angular sensor (gyroscope) to track the whereabouts and movement of an object. Accelerometer sensor is one that has undergone a lot of progress and applied to measure the slope, vibration, acceleration, and position. Accelerometer can also be applied to the measurement of earthquake activity and electronic equipment, such as 3-dimensional game, computer mouse, and telephone. For further applications, sensors are widely used for the purposes of navigate in relation to the position of objects. This final project perform design and manufacture of instrumentation accelerometer as one component of IMU to detect the position / distance with 3 degrees of freedom. Data obtained from the position of the double integral of the accelerometer output in the form of acceleration. Instrumentation system consists of an accelerometer sensor, signal conditioning, microcontroller ATmega 32 as the main processing unit, and computers that will process data input and display output data using Visual C#, while the g-select function is used to determine which mode to use the accelerometer to minimize error in the measurement. Keyword : Accelerometer, Microcontroller ATmega 32, Double Integral, Position